Pemenuhan Hak Atas Air Bersih Terhadap Masyarakat Kabupaten Gresik - Mochammad Mochammad* (Universitas Airlangga, 2018)
As an unimportant one that is needed by humans and important for other purposes, the discussion of this thesis related to aid and the use of air is an important problem in life. Water that was once felt abundant and can be used together. More and more populations are increasing. Water needs for the Gresik Regency community in 2018 have only been served by PDAM Giri Tirta in Gresik Regency totaling 11 Districts out of a total of 18 Districts in Gresik Regency. The fulfillment of the right to clean water for the people of Gresik Regency must always be pursued in line with the increase in population and development of industrial areas. However, related to the completion of clean water for the community, the need for investment funds is not small for the construction of SPAM supporting infrastructure. Related to what is stated in article 2 paragraph (1) of the Covenant on Ecosob rights. The policy of fulfilling the right to clean water for the people of Gresik Regency is implemented by increasing production capacity. The need for investment funds that are not small to build SPAM infrastructure and limited government funds has implications for the implementation of Cooperation between the Government and the Private Sector (KPS). carried out by PDAM Giri Tirta of Gresik Regency as the executor of the provision of SPAM with Business Entities using a system of Cooperation to Build, Operate and Transfer (BOT). Regulation of the Minister of Public Works and Public Housing Number 19 / PRT / M / 2016 concerning Provision of Support by Regional Governments in Collaborating in the Implementation of Drinking Water Supply Systems.